THE DRYING KINETICS AND CHARACTERISTICS OF SHRIMP DRIED BY CONVENTIONAL METHODS - Ersan, Ali Can; Tugrul, Nurcan (ASSOC CHEMICAL ENG, 2021)
The main purpose of this study was to research the influence of different drying methods on the physical and qualitative properties of dried shrimps. Shrimps were dried with conventional methods at 60, 70 and 80 degrees C between 330 to 210 min and 190 to 110 min, in an oven and vacuum oven respectively. Drying time was shortened with the use of a vacuum pump. The drying kinetics of the shrimp were studied, and effective moisture diffusion and activation energy were calculated for both methods. The Alibas model and the Midilli and Kucuk model provided the best experimental data with a high coefficient of determination (R-2) for the oven and vacuum oven techniques, respectively. The final dried products were characterized by investigating the color characteristics, heavy metal content and by carrying out protein analyses. The rehydration ratio was also determined for the dehydrated shrimps. Doting conditions affected the color features so that shrimps dried in ovens and vacuum ovens showed an increase in brightness and yellowness values and a decrease in redness values. The concentration of As, Pb, Cd, Hg, Cu, Zn and Fe in the dried shrimp were within acceptable limits. The protein content of dried shrimp (similar to 85%) is higher than that of undried shrimp (similar to 20%).
Keywords: shrimp; drying kinetics; rehydration; protein content; color analysis; heavy metal; MOISTURE DIFFUSIVITY; MICROWAVE; ENERGY; MODEL; SEA; AIR; Chemistry; Engineering